Hypobaric Hypoxia Imbalances Mitochondrial Dynamics in Rat Brain Hippocampus. (5th July 2015) - Jain, Khushbu; Prasad, Dipti; Singh, Shashi Bala; Kohli, Ekta
Abstract : Brain is predominantly susceptible to oxidative stress and mitochondrial dysfunction during hypobaric hypoxia, and therefore undergoes neurodegeneration due to energy crisis. Evidences illustrate a high degree of association for mitochondrial fusion/fission imbalance and mitochondrial dysfunction. Mitochondrial fusion/fission is a recently reported dynamic mechanism which frequently occurs among cellular mitochondrial network. Hence, the study investigated the temporal alteration and involvement of abnormal mitochondrial dynamics (fusion/fission) along with disturbed mitochondrial functionality during chronic exposure to hypobaric hypoxia (HH). The Sprague-Dawley rats were exposed to simulated high altitude equivalent to 25000 ft for 3, 7, 14, 21, and 28 days. Mitochondrial morphology, distribution within neurons, enzyme activity of respiratory complexes, Δ ψ m, ADP: ATP, and expression of fission/fusion key proteins were determined. Results demonstrated HH induced alteration in mitochondrial morphology by damaged, small mitochondria observed in neurons with disturbance of mitochondrial functionality and reduced mitochondrial density in neuronal processes manifested by excessive mitochondrial fragmentation (fission) and decreased mitochondrial fusion as compared to unexposed rat brain hippocampus. The study suggested that imbalance in mitochondrial dynamics is one of the noteworthy mechanisms occurring in hippocampal neurons during HH insult.